(untitled) (Research, Society and Development, 2022)
Objective: To epidemiologically analyze the process of evaluating potential for effective organ and tissue donors in public health services in Campo Grande, capital of the state of Mato Grosso do Sul. Materials and method: Epidemiological, observational study with a prospective cohort design. Data will be collected from June 1, 2021 to June 31, 2022 through a structured questionnaire. Statistical analysis will be performed according to the nature of the variables, with application of parametric and non-parametric statistical tests. The statistical significance level of 0.05 will be adopted. Expected results: At the end of the research, the aim is to identify any gaps in the maintenance of the potential donor (PD) and direct strategies to improve these measures, with a view to achieving success in the donation process. Finally, it is expected to achieve the favoring of treatment, cure or improvement in the quality of life of patients with chronic conditions waiting for an organ, where scientific production will allow to corroborate with the daily practices to the PD and direct the therapeutic measures to be taken. applied to this individual by managers and health professionals.